2024
DOI: 10.3390/microorganisms12010222
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori: A Contemporary Perspective on Pathogenesis, Diagnosis and Treatment Strategies

Asghar Ali,
Khalid I. AlHussaini

Abstract: Helicobacter pylori (H. pylori) is a Gram-negative bacterium that colonizes the gastric mucosa and is associated with various gastrointestinal disorders. H. pylori is a pervasive pathogen, infecting nearly 50% of the world’s population, and presents a substantial concern due to its link with gastric cancer, ranking as the third most common cause of global cancer-related mortality. This review article provides an updated and comprehensive overview of the current understanding of H. pylori infection, focusing on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 148 publications
0
5
0
Order By: Relevance
“…In the context of dysbiosis, Clostridium difficile , which typically colonizes asymptomatic individuals, becomes a hazardous pathogen. However, there are several micro-organisms that have the potential to become harmful to the gastrointestinal mucosa [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of dysbiosis, Clostridium difficile , which typically colonizes asymptomatic individuals, becomes a hazardous pathogen. However, there are several micro-organisms that have the potential to become harmful to the gastrointestinal mucosa [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, alternative strategies for the treatment of H. pylori infection, such as vaccination, nanotechnology, probiotics, and testing of the bacterium’s sensitivity to antibiotics, have been investigated. New diagnostic methods have also been tested, e.g., multiplex PCR, fecal microbiome analysis, and confocal laser endomicroscopy [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori ( H. pylori ) was recognized a number of years ago as the cause of chronic inflammation in the human gastric mucosa [ 1 ]. Numerous studies have confirmed that neoplasms of the stomach are associated with H. pylori infection [ 2 , 3 , 4 ]. According to the literature, approximately 50.0% of the world’s population is affected by H. pylori infection, and its prevalence varies depending on the geographical area and the method used to prove the infection [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) is a gram-negative, helicalshaped bacterium with flagella, which confer motility enabling it to penetrate the protective mucosal layer and colonize the gastric epithelium [1][2][3][4][5]. It is estimated that half of the world population is infected by H. pylori, but the global prevalence varies significantly between countries and regions [6,7].…”
Section: Introductionmentioning
confidence: 99%